Face Masks, Yeast, and Toilet Paper: Panic Purchases and Stockpiling - Hendrik Hakenes (ZBW - Leibniz Information Centre for Economics, 2021)
During the COVID-19 pandemic, some goods suddenly became scarce due to panic purchases and stockpiling. The decision to hoard is influenced by higher-order beliefs. If an agent believes that other agents think that a good will become scarce, she concludes that these other agents will hoard, and thus tries to preempt them by hoarding herself. To capture such behaviour, we construct a model with a global game. Agents receive noisy information about some variable that influences supply or demand. They then form higher-order beliefs, and possibly panic and hoard the product. We analyze determinants of such panics. Endogenizing prices and quantities, we show that producers with market power set prices strategically to induce panics and thus boost demand. Absent market power, strong competition leads to low prices and thus little overproduction, also causing panics. We also consider firms who need the scarce good as an intermediate product in their production chain, and show that a regulator would require such firms to stockpile the product, thus increasing resilience.
Keywords: L15; L11; I11; 330; Stockpiling; hoarding; panic purchases; scarce goods; price stickiness; COVID-19; resilience